The Influence of Digital Marketing, Brand Image, and Price on Students’ Interest in Choosing Mikroskil University (Case Study at the Faculty of Business 2024-2025) - Jennisca Wijaya; Michelle Michelle; Wendy Utomo; Litka Tiadoraria Br Ginting (Dinasti Publisher, 2025)
This research aims to analyze the influence of digital marketing, brand image, and price on students’ interest in choosing Universitas Mikroskil, particularly in the Faculty of Business. The background of the study highlights the increasing competition among universities in attracting new students. A quantitative method was used, involving a survey of prospective students who have considered enrolling at Universitas Mikroskil. Data collection was conducted using questionnaires, and data were analyzed through the SmartPLS 4.0 application. The results show that digital marketing, brand image, and price each have a significant positive effect on students' interest in choosing a university. Furthermore, the combined influence of these three variables strongly determines students' purchase intention in the context of higher education. The study concludes that universities must enhance their digital marketing strategies, build a strong and consistent brand image, and offer competitive pricing to attract prospective students effectively. These findings are expected to assist higher education institutions in formulating more targeted marketing strategies to increase student enrollment.